Simplified methods of dynamic analysis for guyed towers under the action of extreme winds. - Martín Rodríguez, Patricia; Parnás, Vivian Elena (Rev. Téc. Fac. Ing. Univ. Zulia)
This research deals with the structural behavior of a guyed mast considering the dynamic effect of wind loads. Wind loads are calculated according Cuban code requirements for wind action on structures. The guyed mast is analyzed applying two alternative simplified methods. Structure is analyzed through a non linear geometric analysis. Internal forces in mast members, guys and anchors obtained as a result of the application of the two simplified methods are compared and discussed.